Legislative Regulation and Practice of Imposition of Punishment in the Form of Fine and Forfeiture for the Corruption-Related Crimes in the Republic of Kazakhstan - KUMARBEKKYZY, Zhaniya; ALIBEKOVA, Assel Muratovna; FILIPETS, Oxana Borisovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
For corruption offenses in the Republic of Kazakhstan administrative and criminal responsibility is stipulated. Criminal responsibility is the strictest legal mean of responding to the manifestations of corruption. Kazakhstan undertakes system legal, organizational and institutional measures of anti-corruption management. At the same time the aim of improving the efficiency of the anti-corruption policy requires active involvement in it of the civil society institutions. The practitioners positively estimate the innovation of multiple fines and only approve the transition of forfeiture of the property obtained by illegal means. So, the methods of the definition of illegal origin of the property should be developed. In these issues the experience of the foreign countries may be useful for Kazakhstan.
Keywords: corruption; anti-corruption legislation; criminal responsibility; Criminal Code; civil society institutions